Inducing of direct shoot regeneration during the genetic transformation of tobacco with Agrobacterium rhizogenes strain K599 - E.A. Baimukhametova; Z.A. Berezhneva; Kh.G. Musin; D.Yu. Shvets; A.V. Knyazev; B.R. Kuluev (Учёные записки Казанского университета: Серия Естественные науки)
This article is devoted to the study of the phenotypic manifestations of transformation induced by the Agrobacterium rhizogenes strain K599 in Nicotiana tabacum L., a model plant sensitive to agrobacteria. For this purpose, we carried out a genetic transformation of tobacco leaf disks that resulted in spontaneous callus and shoot formation on hormone-free media. On average, 6 regenerated shoots per leaf explant were obtained. Overall, 2 out of 87 transplanted shoots spontaneously formed roots, and 21 shoots died. In the remaining shoots, rooting was observed only when the growth regulator IAA was added to the medium. Using the above protocol, a total of 39 transgenic plantlets adapted to the given soil conditions were produced from spontaneous points of regeneration. The transformation also initiated the formation of hairy roots, but there were very few of them – 0.77 roots per explant on average. The isolated cultures of tobacco hairy roots generated using strain K599 did not phenotypically differ from those induced by strains A4 and 15834. On the hairy roots, 10 shoots transgenic for rol genes were regenerated by the induction of shoots using growth regulators, 8 of them were later rooted and acclimated to the given soil conditions. The PCR analysis showed the presence of rol genes in all transgenic plants that regenerated spontaneously or were induced on roots by growth regulators. Thus, strain K599, unlike other strains of A. rhizogenes, has a potential to be used to grow transgenic tobacco plants on hormone-free nutrient media by direct regeneration of shoots on explants.